Análisis de factores asociados al rendimiento académico: una aplicación de técnicas demográficas (2000)
The main objective of the present investigation was to describe the academic factors characterizing Psychology Faculty students at Universidad Católica de Colombia. For that purpose, a descriptive design by means of demographic techniques was used. The information was supplied by the Admission Department of the University and the data were analyzed through Access under Windows 7.0 and S.PS.S 6.1. The ob¬tained results allow us to identify and evaluate academic performance for this popu¬lation. It was found that the general average for this period was 3.71/5.0 and that this average is higher from the sixth semester. In an overall level, it was observed that the averages for groups studying in the evening are slightly higher than the groups study¬ing in the morning and Research was identified as the area with higher average with 4.43 The rate for academic deficiency was 1.57% and for excellency was 39.06%, that is, 440 students of the population. Another established indicator was subject failure corresponding to 8.63%.